An In-vitro Comparison of the Shear Bond Strengths of Two Different Gingival Colored Materials Bonded to Titanium Alloy Discs and Acrylic Artificial Teeth. - Elzarug, Yahya. (2017)
Abstract: Abstract Purpose The purpose of this study was to compare shear bond strengths between two different gingival colored materials bonded to titanium alloy discs and acrylic resin artificial teeth. Materials and Methods For the first part of the study, 30 titanium alloy disc specimens were embedded in autopolymerizing resin. These discs were then divided randomly into two groups: 1. Heat Cure (HT1) and 2. Pink Composite (CT1). The discs were sand-blasted with 100 microns aluminum oxide particles. For the HT1 group and utilizing silicone molds, wax up was performed. After wax removal step, heat-cure acrylic resin was applied and processed according to the manufacturer's recommendations. For the CT1 group and utilizing silicone molds, metal primer II and gum opaque were applied and light cured; pink composite was then applied and light cured. For the second part of the study, 30 artificial resin first molar teeth were completely embedded in autopolymerizing resin. Teeth were then divided randomly into two groups: 1. Heat Cure (HT2) and 2. Pink Composite (CT2). For the HT2 group and utilizing silicone molds, wax up was performed. Samples were then transferred to be processed in the heat-cure acrylic resin according to the manufacturer's recommendations. For the CT2 group and utilizing silicone molds, composite primer followed by pink composite were applied and light cured. Shear bond tests were performed, using a universal testing machine Instron 3345. The shear load at the point of failure was recorded in Newtons. The force was calculated in MPa by calculating the failure load divided by the surface area. Two independent- samples t-tests were performed. A significance level of P < 0.05 was used for comparison. Results This study revealed that the difference in the shear bond strengths of two different gingival colored materials bonded to titanium discs was statistically significant (p-value = .012). The difference in the shear bond strengths of two different gingival colored materials bonded to acrylic teeth was statistically significant (p-value < .001). Conclusion In this in vitro study, heat-cured acrylic resins exhibited higher bonding strengths when bonded to titanium discs or acrylic artificial teeth in comparison to pink composite resins.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Other.; Advisor: Roger Galburt.; Committee: Hamasat Gheddaf Dam, Matthew Finkelman, and Ala Ali.; Keyword: Dentistry.